The role of microendodontics in treating mandibular second molar with five canals - Harry Huiz Peeters (Dental Journal (Majalah Kedokteran Gigi), 2009)
Background: Finding the incidence of anatomical variation in daily practice becomes more frequent due to the development of diagnostic tools such as microscopes and ultrasonic devices. Therefore, a thorough understanding of the normal anatomy of canals and its variations in root canal treatments would be helpful in achieving the desired result. The usual root configuration of a mandibular second molar is two separate roots, distal and mesial, of which the distal root usually has one canal and the mesial root two canals. The incidence of 4 distinct root canals in the distal root of C-shaped orifices is a rare phenomenon that is reported in literature. Purpose: To understand the role of microendodontics in trating mandibulary second molar with five canals. Case: This case shows how to locate and manage a rare anatomical variation of mandibular second molar with 4 distinct root canals in the distal aspect of a C-shaped orifice successfully. Case Management: The anatomical variation was overcome with the help of diagnostic tools such as microscopes and ultrasonic tips. Conclusion: The successful treatment of this case demonstrates the necessity for awareness of the presence of additional canals and abnormal morphology of the canals. Besides that the operator’s perseverance and patience as well as sophisticated diagnostic tools, such as the dental operating microscopes and ultrasonic tips, have an important role in treating unusual configurations of root canals.